Supply Chain Collaboration with Overseas Suppliers in Westcoast One Derby Ltd. - Dhanasekaran, Mohanraj (2012)
ABSTRACT The aim of this research is to examine supply chain collaboration with overseas suppliers in Westcoast one derby Ltd. The main objectives of the research is to study the information sharing and trust building between the buyer and supplier collaboration; to examine the SCC and the benefits of SCC in Westcoast one derby Ltd. This research is based on qualitative methods. To examine collaboration in supply chain management, a fashion retailer company (Westcoast One) which engage in collaborative supply chain with their overseas suppliers in China and Pakistan is chosen. First the buyer company Westcoast one will be studied in detail; the company background, company operation and their collaboration. Then their current collaborative practice will be studied through questionnaires. By analysing the literature in supply chain collaboration, we have identified a key finding the information sharing between buyer and supplier builds trust between both partners; which eventually leads to successful collaboration and customer satisfaction. Many companies try to set up collaborative practices to compete in their business but many fails. The main reason is a lack of willingness to share information results in failure of collaboration. This dissertation tries to find out the gap in information sharing and trust in Westcoast one with their suppliers; how IT integration helps to achieve greater benefits in supply chain collaboration. The recommendation from the findings will help Westcoast one to improve the collaboration with their suppliers without any risk and will be able to increase the overall supply chain efficiency in their collaboration. Key words: Supply Chain Collaboration, Information Sharing, and Trust